(untitled) (American Journal of Islam and Society, 2000)
Although Islam is the youngest of the three Abrahamic religions, it bas succeeded in making breakthroughs in all comers of the globe. Today, it is the fastest growing religion in the world. and its presence has become a recognized fact in rich industrialized nations like the United States. In the book under review, Professor Sulayman Nyang examines the arrival and development of Islam in America and asserts that it will stand permanently side-by-side with Christianity and Judaism and that these religions will co-exist peacefully. In the first chapter. the author tells the story of the African Muslim slaves in North America. The discovery of the New World by Columbus resulted in the transplantation of millions of African slaves to work in the plantations of white settler farmers. A large number of slaves were captured in West Africa - a region where Islam had already become firmly rooted. However, the nature of slavery itself (as it was practiced in America) and the separation of the children from their Muslim parents impeded the take-off process of Islam in America. These were also critical times for the African Muslim slaves, as they were not allowed to practice their religion freely. This lack of religious tolerance forced many of the slaves to convert to Christianity, which was the faith of their "masters." The author also mentions the wave of Muslim immigrants that occurred during the frrst quarter of the twentieth century and involved people from the Middle East, North Africa, southern and central Asia, and southern and central Europe. Some of these immigrants returned home after the war, but many decided to stay in the United States in order to pursue the American Dream. The next turning point for Islam was the Islamic Revolution, which broke out in Iran in 1979 and had a very strong impact in the United States due to the country’s close alliance with the ousted Shah ...